How successful are we aging - Filiz POLAT; Leyla Delibaş (My University, 2021)
Aim: This study was conducted to determine who live in southeastern Turkey, the older people how successful they get older.Methods: The sample of the descriptive study; it consisted of 442 elderly individuals aged 60 and over who applied to two FamilyHealth Centers (FHC) between July and October 2019. Personal Information Form and Successful Aging Scale were used to collectdata. Percentage, frequency, average, standard deviation, linear regresyon, t test and Anova were performed in the data analysis(p<0.05).Results: It was determined that the mean scores of Successful Aging Scale decreased with increasing age, increased with educationand the difference between them was significant (p=0.00). It was determined that Successful Aging Scale total scale mean scorewas 46.5±12.0. The effect of independent variables on successful aging was determined as R2 = .262.Conclusion: It was determined that total mean score of successful aging of the elderly individuals included in the study wasmedium, and as the age increased, the mean score of successful aging decreased.
Keywords: Successful Aging; Old Age Period